When Outpatient Care Is Not Enough: Successful Use of an Inpatient Behavioral Intervention for a Child With ARFID. (December 2018) - Lenz, Katrina R.; Mitan, Laurie A.; Kleinhenz, Susan R.; Matthews, Abigail
Avoidant/restrictive food intake disorder (ARFID) is characterized by restrictive eating in the absence of body image disturbance or drive for thinness, resulting in the persistent failure to meet appropriate nutritional and/or energy needs and/or psychosocial impairment. ARFID is a heterogeneous diagnosis with diverse etiologies. Thus, identification of best practice guidelines and evidence-based treatments for ARFID is challenging and, to our knowledge, randomized treatment studies have not been published. Existing literature promotes a multidisciplinary care approach that integrates behavioral, cognitive behavioral, and family-based interventions. In this report, we present the case of an 8-year-old female with ARFID who began restricting her food and fluid intake following a viral illness. The patient also choked on a lozenge at school and peers laughed in response, resulting in heightened fears of eating, subsequent dehydration, and admission to a gastroenterology unit at a pediatric hospital. While hospitalized, she was diagnosed with ARFID, a nasogastric tube (NGT) was placed, and was referred to outpatient eating disorder specialists. Despite participating in 16-outpatient therapy sessions, progress was limited and the patient was medically admitted to safely remove the NGT in the context of behavioral interventions targeting food refusal. This case report describes the successful use of an intensive inpatient behavioral intervention used for the patient, which resulted in the rapid resumption of food and fluid intake, by mouth. This case study supports the use of such intervention for ARFID when sufficient progress is not achieved in outpatient care.